(untitled) (Research, Society and Development, 2020)
Objective: To know which strategies are used by professionals to encourage exclusive breastfeeding. Method: qualitative research, exploratory descriptive, carried out with nine active participants in a Family Health Strategy team, in a city in the central region of Rio Grande do Sul. Semi-structured interviews were recorded and transcribed. The treatment of the data carried out through the discourse analysis proposed by Minayo. Results: according to the report, three categories emerged: Strategies used to promote breastfeeding in the Family Health Strategy; The power of breastfeeding in the view of health professionals and Challenge for exclusive breastfeeding: from technique to health education. Final considerations: evidenced the need to enhance the care for pregnant women and nursing mothers regarding health education, contemplating the management in face of the challenges imposed by breastfeeding.